The Multitemporal Study Soil Use and Coverage Under the Sector High in El Oro Province Using GIS (Revista Científica Ciencias Naturales y Ambientales, 2012)
This study examines the use of GIS and Remote Sensing techniques to detect land use /cover change in Bajo Alto in the province of El Oro in 1977, 2003 and 2010. The more significant affected coverage was mangrove, it was severely deforested, this may suggest that was caused by the "shrimp's farming boom” of 1977. Mangrove leaded the table of land distribution in 1977 with 59% and in 2010 only represents 18% of classes. The community has been interested in the preservation of the mangrove in the period 2003 – 2010, the evidence is presented with the increase of 2% of mangrove coverage. Also is worth to mention that the main threat to mangroves has been and still remains, the construction of shrimp pools, this layer leads in the total distribution of 2003 and 2010 with 76% and 77% respectively. Basic statistics were used to determine the growthpercent of the layer settlements, these results were related to the Gas (GLP) plant of Petro Ecuador which have been generating job opportunities to the community and moreover.
Keywords: Mangroves; settlements; liquefaction; remote sensing; preservation